2006
DOI: 10.1038/sj.eye.6702241
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of reattached macula in nine cases with excellent Snellen acuities

Abstract: Purpose To compare the macular functions of patients with excellent visual acuity after retinal detachment (RD) surgery, with the healthy fellow eye. Methods Of 214 patients, nine patients, who were successfully operated because of unilateral RD involving the macula and achieved excellent visual acuity, were analysed. The fellow eyes of the patients were taken as the control group. The macular functions were evaluated with visual acuity, contrast sensitivity, colour vision, visual field, and pattern VEP in ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…41 Using similar methods, Ozgür and Esgin reviewed 9 patients following-scleral buckle RD repair with BCVA better than log MAR 0.8 and found CS in RD eyes to be reduced compared with the healthy fellow eyes, yet to a nonstatistically significant degree. 43 Kawamura et al demonstrated lower CS in 36 macula-off RRD eyes with a postoperative BCVA of greater than 1.0 compared with macula-on RRD eyes following surgery. 42 The latter group used a Takagi glare tester CGT-2000 to measure CS, which has been shown to have relatively poor accuracy and repeatability.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…41 Using similar methods, Ozgür and Esgin reviewed 9 patients following-scleral buckle RD repair with BCVA better than log MAR 0.8 and found CS in RD eyes to be reduced compared with the healthy fellow eyes, yet to a nonstatistically significant degree. 43 Kawamura et al demonstrated lower CS in 36 macula-off RRD eyes with a postoperative BCVA of greater than 1.0 compared with macula-on RRD eyes following surgery. 42 The latter group used a Takagi glare tester CGT-2000 to measure CS, which has been shown to have relatively poor accuracy and repeatability.…”
Section: Discussionmentioning
confidence: 97%
“…[36][37][38] Using the 25-item National Eye Institute Visual Function Questionnaire in patients with RRD, 39 Okamoto et al reported vision-related quality of life to be significantly correlated with postoperative CS measured by preprinted letter charts, yet no correlation was found between vision-related quality of life and postoperative VA. 40 Several previous reports have shown reduced CS in patients with RRD using preprinted letter charts. [41][42][43] Despite measuring CS using methods with poor range and resolution for sampling target contrast and frequency [28][29][30] and poor test-retest reliability, 29,31,32 those reports demonstrated the detrimental effect of RD on CS.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the longer the duration of macular detachment, the lower the contrast sensitivity score. 25 However, at the single-cell level, little physiological data are available on how ganglion cells respond to RD. Therefore, we went on to investigate the contrast threshold of Y cells in normal and detached retinas.…”
Section: Contrast Thresholdmentioning
confidence: 99%
“…This quick decline in luminance sensitivity could be attributed to factors such as hypoxia, gradual photoreceptor apoptosis, and reattachment. Hypoxia is created by physically separating the retina from its choroidal blood supply, 18,25,32 causing fluid accumulation between the retinal pigment epithelium and the detached retina. Excess fluid under the retina Comparison of average contrast threshold in normal and detached retinas.…”
Section: Rd Impact On Y Cellsmentioning
confidence: 99%